The forbidden door ebook - Koontz, Dean (Jane Hawk, 2018)
NEW YORK TIMES BESTSELLER • When this relentless rogue FBI agent comes knocking, her adversaries will have to answer—with their lives—in this thrilling Jane Hawk novel by the #1 New York Times bestselling author of The Silent Corner . “Koontz continues the incredible saga of the robust character of Jane Hawk, and it’s as terrific as the others in the series.”—Associated Press “We’re rewriting the play, and the play is this country, the world, the future. We break Jane’s heart, we’ll also break her will.”   She was one of the FBI’s top agents until she became the nation’s most-wanted fugitive. Now Jane Hawk may be all that stands between a free nation and its enslavement by a powerful secret society’s terrifying mind-control technology. She couldn’t save her husband, or the others whose lives have been destroyed, but equipped with superior tactical and survival skills—and the fury born of a broken heart and a hunger for justice—Jane has struck major blows against the insidious cabal. But Jane’s enemies are about to hit back hard. If their best operatives can’t outrun her, they mean to bring her running to them, using her five-year-old son as bait. Jane knows there’s no underestimating their capabilities, but she must battle her way back across the country to the remote shelter where her boy is safely hidden . . . for now. As she moves resolutely forward, new threats begin to emerge: a growing number of brain-altered victims driven hopelessly, violently insane. With the madness spreading like a virus, the war between Jane and her enemies will become a fight for all their lives—against the lethal terror unleashed from behind the forbidden door. Don’t miss any of Dean Koontz’s gripping Jane Hawk thrillers: THE SILENT CORNER • THE WHISPERING ROOM • THE CROOKED STAIRCASE • THE FORBIDDEN DOOR • THE NIGHT WINDOW Praise for The Forbidden Door “Compelling and enthralling.” — New York Journal of Books “Mind-blowing. . . [a] gripping series . . .  a thrill ride. [Dean Koontz is] able to distract you for hours.” — Bookreporter “Koontz is on another roll with a new series that boasts a juicy premise and a compelling star. . . . Pure gold.” — Booklist